Histological and histochemical features of the mature female reproductive tract of local breed dog (Canis familiaris) - Abood, Dhyaa Ab; Dawood, Mohammed Sulaiman; Yousif, Noor Hussein; Karim, Abdulkarim Jafar (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Many studies focused on clinical cases such as ovariohysterectomy of bitches and scarcely mentioned the histological features. The present study describes the cytoarchitecture characteristics of a local dog’s mature adult reproductive tract. Materials and Methods: Sixteen samples of uterus and cervix were obtained from local breed bitches to conduct this study. The organs were processed according to routine histopathological protocol and stained with hematoxylin and eosin, Masson’s trichrome, and combined Alcian blue (2.5 pH) and PAS (AB-PAS) stains. Results: The mature endometrium formed numerous short epithelial folds and epithelial crypts composed of mucous cells and cuboidal cells. The core of the endometrium is composed of fibrous tissue containing fibroblasts with discernible active uterine glands. The myometrium is constructed by thick, circularly, and longitudinally oriented layers of smooth muscle fibers. The AB-PAS stain of the uterine glands revealed light-neutral glycoprotein. The cervix had a very thick wall and displayed numerous huge mucosal folds, covered by ciliated and non-ciliated pseudo-stratified epithelium. The tissue core of the cervix was very thick, and composed of highly cellular, highly vascular, and non-glandular fibrous connective tissue. Layers forming the muscularis of the cervix are composed of circularly, obliquely, and longitudinally oriented smooth muscle bundles. The cervical epithelial cells revealed a light film of neutral glycoprotein that covered the epithelial surface, and the goblet cells denoted strong acidic mucopolysaccharide. Conclusions: The current study concluded that the most mature nonpregnant local breed dogs during the proestrus and estrus phases had an active endometrial architecture that is suitable for the management of reproduction. J. Adv. Vet. Anim. Res., 11(4): 835–845, December 2024 http://doi.org/10.5455/javar.2024.k835